Study on Status of Serum Biochemical and Hematological Parameters in COVID-19 Positive Patients Attending a Tertiary Care Hospital - Shreewastav, R. K.; Singh, G. K.; Jha, K. K.; Yadav, R. K.; Gharti, S. B. (Kathmandu University Medical Journal, 2022)
Background Coronavirus disease 2019 (COVID-19) presents clinically a variety of pathological and clinical organ dysfunctions, ranging in severity from asymptomatic to fatal. The care and monitoring of COVID-19 patients may benefit from the use of biochemical and hematological markers. Objective To observe the alteration of serum biochemical and hematological parameters in COVID-19 positive patients, attending a Tertiary Care Hospital. Method A descriptive cross-sectional study was conducted on all COVID-19 positive patients attending Nobel Medical College Teaching Hospital, Biratnagar, Nepal from 15th December 2021 to 15th February 2022. The test results of different serum biochemical and hematological parameters done for these patients were recorded in clinical laboratory services and obtained retrospectively for the analysis. The data were entered in MS excel and analyzed by SPSS version 20. Result Out of 1537 COVID-11699 declared positive patients, 712 (46.32%) were male and 825 (53.68%) female. Mean age of COVID positive patients was 40.03±20.08 years. The level of serum SGOT, SGPT, ALP and GGT was significantly elevated in 39.9%, 42.8%, 32.3% and 47.2% of COVID positive patients respectively. Blood Urea, creatinine, uric acid and sugar level were significantly elevated in 63%, 56.1%, 33.1% and 47.6% patients respectively. The serum level of LDH, D-dimer, CRP and procalcitonin (PCT) were significantly increased in 52.1%, 75.9%, 71.6% and 61.2% of patients respectively. The serum value of total cholesterol, triglyceride, HDL and LDL were significantly lowered in 52.2%, 43.8%, 70.1% and 60.3% of patients respectively. RBC concentration and level of hemoglobin was reduced in 56.6% and 53.6% of COVID positive patients respectively whereas total leukocyte count was elevated in 80.7% with increase in neutrophil in 87.9% and decrease in lymphocyte in 79.4%. Conclusion A portion of COVID-19 positive patients showed drastically altered test results for various serum biochemical and hematological markers, although many of them had normal findings.